1977
DOI: 10.1139/v77-532
|View full text |Cite
|
Sign up to set email alerts
|

Migration of hydroxyl in secondary systems during solvolysis in acid solution

Abstract: Can. J. Chem. 55,3774 (1977). A system of compounds has been prepared which is well adapted for displaying the role of trans vicinal, secondary hydroxyl in solvolysis. On methanolysis in acid solution, compounds 5, 7a, and 8a all gave the same products, 9a and 10a, and in practically the same proportions, suggesting that at least one intermediate was common to all three reactions. These intermediates were such that 7a and 8u were not interconverted during the solvolysis, a fact in support of 6 as a common inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In a previous study of deoxygenation of trans-1,2-cyclohexanediol using an organometallic catalyst, it was suggested that dehydration might proceed via an epoxide intermediate. 38,51,52 No epoxide is detected in the products of the current reaction, but this does not rule out an epoxide intermediate because it could undergo rapid hydrolysis. 53 To test for the intermediacy of an epoxide, hydrothermal reaction was performed starting with 1,2-epoxycyclohexane under the same conditions as the diol reactions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In a previous study of deoxygenation of trans-1,2-cyclohexanediol using an organometallic catalyst, it was suggested that dehydration might proceed via an epoxide intermediate. 38,51,52 No epoxide is detected in the products of the current reaction, but this does not rule out an epoxide intermediate because it could undergo rapid hydrolysis. 53 To test for the intermediacy of an epoxide, hydrothermal reaction was performed starting with 1,2-epoxycyclohexane under the same conditions as the diol reactions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The preparation of compounds used in this work, when not reported here, can be found in earlier papers (7,8,10 and references cited therein). Epoxides 14 and 15 and 17 and 18 were each free of their respective isomers and had a purity of better than 99.9%.…”
Section: Compounds Prepared Preuiouslymentioning
confidence: 99%